Investigations on the rate performance of LiFePO4/CeO2 composite materials via polyol technique for rechargeable lithium batteries. Issue 105 (12th October 2015) - Sivakumar, M.; Muruganantham, R.; Subadevi, R.
Abstract : Surface modification of LiFePO4 using CeO2 cathode materials has been prepared by polyol technique with a chemical combination route. CeO2 has been formed as solid solution on LiFePO4 surface, which provides better EC performances. Abstract : An attempt has been made to synthesize CeO2 modified LiFePO4 composite cathode materials via a polyol technique with a chemical combination route. The surface modified LiFePO4 samples exhibit superior electrochemical performances compared to bare samples. CeO2 may help to induce the fast lithium-ion diffusivity of LiFePO4 cathode materials to promote high-rate stable cycling and a good coulombic efficiency. The complete coverage of a mild coating of CeO2 under an optimized concentration on LiFePO4 may limit the direct contact of the active material with the electrolyte, which improves the interface stability by preventing the dissolution of Fe ions in the electrolyte.